Bacteremia caused by cellulosimicrobium in a bone marrow transplant patient: A case report and literature review. (2018) - Gonzales Zamora, Jose Armando; Camps, Nicholas
Abstract: Background: Cellulosimicrobium sp. is a ubiquitous gram-positive bacillus that was formerly known as Oerskovia. This bacterium is found in soil and decaying plant material and is rarely associated with infections in humans. Case report: We report the case of a 44 year-old woman with history of bone marrow transplant that developed Cellulosimicrobium sp. bacteremia secondary to a central line infection. She was admitted with presumed sepsis. Blood cultures from central line and periphery revealed the growth of gram-positive rods that were further identified as Cellulosimicrobium sp . by MALDI-TOF. She was treated with vancomycin and line removal. Microbiologic cure was achieved; however, she developed hospital-acquired pneumonia, which led to a fatal outcome. Conclusion: To our knowledge, there are only 15 documented cases of Cellulosimicrobium sp. bacteremia. Our case illustrates the potential pathogenicity of this bacterium and the importance of appropriate antimicrobial therapy and removal of infected central catheters. It is essential to know that gram-positive bacilli should not be disregarded as contaminants when recovered from multiple blood cultures. In this situation, a full microbiologic identification must be attempted.